1996
DOI: 10.1002/(sici)1096-8628(19960503)63:1<243::aid-ajmg42>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular cytogenetic observations in three cases of “trisomy 12p syndrome”

Abstract: Two unpublished cases with partial tandem duplication of 12p and one previously published case were studied by fluorescence in situ hybridization using 11 cosmid DNA probes from 12p. We propose that the smallest duplications of 12(p13.2pter) and 12(p13.1p13.33) produce the “trisomy 12p syndrome” which is characterized by heavy birth weight, macrocephaly, muscular hypotonia, short neck, flat face, high forehead, prominent cheeks, large philtrum, short nose with anteverted nostrils, and broad everted lower lip. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 14 publications
4
47
2
Order By: Relevance
“…Trisomy of the short arm of chromosome 12 is known to cause a recognizable phenotype and has been estimated to occur at a rate of 1 in 50,000 births (Allen et al, 1996;Stengel-Rutkowski et al, 1981). The syndrome often presents with moderate to severe psychomotor retardation, generalized hypotonia and facial dysmorphism characterized by a round face with prominent cheeks, prominent forehead, broad nasal bridge, short upturned nose, long philtrum, thin upper lip, broad everted lower lip, and abnormal ears (Rauch et al, 1996;Tekin et al, 2001;Tsai et al, 2005). In the majority of the cases, the trisomy 12p is inheritance from the malsegregation of a balanced parental translocations leading to varying extents of the trisomic 12p segment and included missing material of another chromosome (Arnaud et al, 1984;Guerrini et al, 1990;Segel et al, 2006;Uchida and Lin, 1973).…”
Section: Discussioncontrasting
confidence: 53%
“…Trisomy of the short arm of chromosome 12 is known to cause a recognizable phenotype and has been estimated to occur at a rate of 1 in 50,000 births (Allen et al, 1996;Stengel-Rutkowski et al, 1981). The syndrome often presents with moderate to severe psychomotor retardation, generalized hypotonia and facial dysmorphism characterized by a round face with prominent cheeks, prominent forehead, broad nasal bridge, short upturned nose, long philtrum, thin upper lip, broad everted lower lip, and abnormal ears (Rauch et al, 1996;Tekin et al, 2001;Tsai et al, 2005). In the majority of the cases, the trisomy 12p is inheritance from the malsegregation of a balanced parental translocations leading to varying extents of the trisomic 12p segment and included missing material of another chromosome (Arnaud et al, 1984;Guerrini et al, 1990;Segel et al, 2006;Uchida and Lin, 1973).…”
Section: Discussioncontrasting
confidence: 53%
“…Due to the instability created by the presence of the second centromere these dicentric chromosomes would undergo a breakage resulting in an inverted duplication chromosome with a distal deletion (Pramparo et al 2004) whereas analphoid chromosomes may be stabilized through the acquirement of a neocentromere (Amor and 25-226.28-230.31 224.30-228.32 226.28-230.34 D12S62 12p12.3 15119370 191.73-193.7-197.79 a 189.72-197.85 191.74-193 Warburton 2004). In fact, all these types of 12p rearrangements have been reported (Schinzel 2001;Dufke et al 2001) but very few have been defined at the molecular level and among the four that have been studied by FISH analysis (Rauch et al 1996;Dufke et al 2001) none have breakpoints within these clusters. However, it seems likely that the 12p LCRs we are describing mediate at least some of the several direct duplications interpreted as dup(12)(pter-p12).…”
Section: Discussionmentioning
confidence: 99%
“…The macrocephaly and thin upper lip might also be the consequence of the partial trisomy 12pter. 61 Batanian et al 62 reported a 5 year old mentally retarded boy with a half cryptic translocation 6qter and 2pter (partial trisomy 2p25.3-pter and monosomy 6qter, the der(6) was microscopically visible) with minor dysmorphic features (epicanthic folds, thin upper lip, flat philtrum, and low set, large ears), which supports the relatively mild phenotypic presentation of submicroscopic 6qter deletions. However, Rossi et al 12 reported a 1 year old child with congenital chylothorax, facial dysmorphism (not further specified), and absence of sacral vertebral fusion caused by a familial der(6)t(6q;16p).…”
Section: -60 6qmentioning
confidence: 96%